Effects of Stem Cutting Time and Height on Yield Components and Yield of Rice Ratun System (Oryza sativa L.) - Vicky Silvia Nuzul (Vegetalika, 2018)
Ratun is the ability of the rice plant to regenerate new tillers after harvest, so it can be increased rice productivity. The aim of this research was to compare the yield components and yield between rice ratun with the parent rice, to analyze influence of stem cutting time and height on yield components and yield of rice ratun system and also to determine optimum cutting time and height for the yield components and yield of rice ratun. This research was heald in Pusat Inovasi Agroteknologi (PIAT) of  Gadjah Mada University, Kalitirto, Berbah, Sleman, Yogyakarta on March to June 2017.  The experiment used split-plot design with cutting time as the main plot and cutting height as sub plot with 3 blocks as replication. The cutting time consisted of 3 levels i.e. at harvest time, 7 days after harvest time, and 14 days after harvest time.  Meanwhile, cutting height consisted of 4 levels i.e. 3 cm, 13 cm, 23 cm, and 33 cm above the ground.The research showed that the yield components and yield of rice ratun lower than the parent rice. Cutting time at harvest time, 7, 14 days after harvest time with the cutting height close to the ground increase yield component and yield of rice ratun but delay the generative phase. The highest yield components and yield of rice ratun achieved at harvest time cutting time with cutting height 3 cm above the ground.